2013
DOI: 10.1007/s10571-013-9940-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs: A Novel Class of Potential Biomarkers for Diagnosing and Prognosing Central Nervous System Diseases

Abstract: As a class of important endogenous small noncoding RNAs that regulate gene expression at the posttranscriptional level, microRNAs (miRNAs) play a critical role in many physiological and pathological processes. It is believed that miRNAs contribute to the development, differentiation, and synaptic plasticity of the neurons, and their dysregulation has been linked to a series of diseases. MiRNAs exist in the tissues and as circulating miRNAs in several body fluids, including plasma or serum, cerebrospinal fluid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 73 publications
1
96
0
1
Order By: Relevance
“…Several studies have reported differential miRNA expression in MS patient-derived specimen or in EAE mouse models (Gandhi et al 2013;Jin et al 2013;Murugaiyan et al 2015;Rao et al 2013;Zare-Shahabadi et al 2013;Zhang et al 2014). Although disease associated miRNAs have been identified in various tissues and body fluids of MS patients or EAE mice (Lescher et al 2012;Thamilarasan et al 2012), no systemic study has been carried out to monitor the changes in miRNA profiles over the disease course starting from predisease to chronic state of the disease state.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported differential miRNA expression in MS patient-derived specimen or in EAE mouse models (Gandhi et al 2013;Jin et al 2013;Murugaiyan et al 2015;Rao et al 2013;Zare-Shahabadi et al 2013;Zhang et al 2014). Although disease associated miRNAs have been identified in various tissues and body fluids of MS patients or EAE mice (Lescher et al 2012;Thamilarasan et al 2012), no systemic study has been carried out to monitor the changes in miRNA profiles over the disease course starting from predisease to chronic state of the disease state.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that circulating miRNAs can be associated with the brain miRNA , and miRNAs released from damaged cells or circulating cells lead to increased plasma miRNAs expressions (Mayr et al 2013). Therefore, serum miRNAs could partly represent the miRNAs released from damaged nerve tissue (Jin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous, small, non-coding RNAs that post-transcriptionally regulate gene expression and are highly expressed in the brain, which have emerged as essential regulators of neuronal development, differentiation, and neuroplasticity [125] miRNAS are present in tissues and in circulating fluids, particularly in the blood and several reports highlight differences of composition in disease states [126]. A peripheral blood compartment that may be particularly relevant are the exosomes, cellular miRNAs-containing secretory vesicles able to attach recipient cells and release miRNAs potentially modulating their function [127].…”
Section: Intercellular Communication Mediated By Micrornasmentioning
confidence: 99%